Literature review: well-being and productivity in Non-industrial workplace design. - López Merchán, Yazmin Elizabeth (Artes: Architecture, Technology and Sustainability, 2024)
Workplace design has gained relevance due to its impact on employees' psychological and physical factors. These spaces not only constitute workplaces but also foster creativity, motivation, and well-being, directly influencing job performance. A properly designed environment can reduce stress and improve productivity, while inappropriate conditions generate adverse effects. Factors such as lighting, acoustics, biophilia, and spatial layout are essential for creating environments that promote both mental health and physical performance. In this context, workplace architecture has evolved, adapting to teleworking and new technologies. Furthermore, unconventional aspects, such as the aromatization of spaces, highlight the need to consider multiple sensory factors in workplace design, with the aim of creating healthy and stimulating environments that enhance employee productivity, performance, and satisfaction. This manuscript compiles the findings of various scientific articles that address the impact of non-industrial workspace design on employee well-being and productivity. Throughout this analysis, we identify current trends, the determining factors of workplace well-being, and how these elements contribute to optimizing productivity through appropriate workspace design.
Keywords: Well-being; Workplace design; health; productivity; job satisfaction